Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.20414/konstan.v6i1.74
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Project Based Learning Terhadap Efikasi Diri dan Kemampuan Berpikir Kritis Peserta Didik

Abstract: Model pembelajaran yang sesuai merupakan bagian penting dalam kegiatan proses belajar dalam mencapai tujuan pembelajaran yang direncanakan. Tujuan artikel penelitian ini adalah mengetahui pengaruh model pembelajaran Project Based Learning (PjBL) terhadap self-efficacy (efikasi diri) dan kemampuan berpikir kritis peserta didik selaku calon pendidik. Jenis penelitian ini adalah kuantitatif berpendekatan kuasi eksperimen dengan one group pretest-postest design dengan teknik purposive sampling. Instrumen yang digu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
0
0
1
Order By: Relevance
“…Students obtained significant scores of 0.000 < 0.05 can be interpreted that H 0 Denied Acceptance H a Based on this, it can be concluded that the learning model Project Based Learning towards science literacy skills and Self-efficacy grade XI student of SMA Negeri 1 Lhokseumawe has an influence. This is in line with what was said by (Ratu et al, 2021) that physics learning uses models project base learning (PjBL) has a positive effect on self-efficacy. It can improve students' critical thinking skills with a significant increase.…”
Section: Statistical Test Analysissupporting
confidence: 91%
“…Students obtained significant scores of 0.000 < 0.05 can be interpreted that H 0 Denied Acceptance H a Based on this, it can be concluded that the learning model Project Based Learning towards science literacy skills and Self-efficacy grade XI student of SMA Negeri 1 Lhokseumawe has an influence. This is in line with what was said by (Ratu et al, 2021) that physics learning uses models project base learning (PjBL) has a positive effect on self-efficacy. It can improve students' critical thinking skills with a significant increase.…”
Section: Statistical Test Analysissupporting
confidence: 91%
“…Sejalan dengan peran besar strategi metakognitif dalam pembelajaran, model pembelajaran PjBL juga merupakan salah satu strategi yang dapat memberdayakan keterampilan metakognitif maupun berrpikir kritis siswa. PjBL menggunakan masalah sebagai jalan untuk mengumpulkan informasi baru dan mengintegrasikannya dengan pengalaman dan kreativitas siswa (Ratu et al, 2021). Pembelajaran berbasis proyek juga dapat memberikan pengalaman langsung dalam menemukan konsep baru, melatih siswa berpikir kritis dan memecahkan masalah, berpikir kreatif, berkolaborasi dengan orang lain, dan memimpin diri sendiri secara efektif (Surya et al, 2018;Zubaidah, 2019a).…”
unclassified